Left ventricular wall thickness and severity of cardiac disease in women and men with transthyretin amyloidosis. (15th March 2023) - Aimo, Alberto; Tomasoni, Daniela; Porcari, Aldostefano; Vergaro, Giuseppe; Castiglione, Vincenzo; Passino, Claudio; Adamo, Marianna; Bellicini, Maria Giulia; Lombardi, Carlo Mario; Nardi, Matilde; Palamara, Gloria; Varrà, Guerino Giuseppe; et al.
Abstract: Aims: Cardiac amyloidosis (CA) is due to a deposition of amyloid fibrils in the heart causing an increase in wall thickness. A left ventricular (LV) wall thickness ≥12 mm plus at least one red flag should raise the suspicion of CA. As normal values of LV wall thickness are lower in women, the adoption or the same cut‐off values for men and women could lead to underdiagnosis or delayed diagnosis in women. We investigated the relationship between LV wall thickness and the severity of cardiac involvement in women and men with transthyretin (ATTR) CA. Methods and results: We evaluated 330 consecutive patients diagnosed with ATTR‐CA at three centres (Pisa, n  = 232; Brescia, n  = 69; Trieste, n  = 29). Interventricular septum (IVS) and posterior wall (PW) thickness values were lower in women ( n  = 53, 16%) than men, but most differences were abolished when indexing by body surface area (BSA), height, or height 2.7, suggesting similar disease severity when accounting for the smaller body size of women. PW thickness indexed for height 2.7 was even higher in women. We also searched for correlations between IVS and PW thickness and other indicators of the severity of cardiac disease. IVS values indexed by height 2.7 displayed tighter associations with N‐terminal pro‐B‐type natriuretic peptide values than non‐indexed IVS values. Similarly, indexed values displayed closer relationships with relative wall thickness, E/e' ratio, and tricuspid annular plane systolic excursion. Conclusions: Indexed LV wall thickness values, particularly by height 2.7, reflect more accurately the severity of cardiac involvement than non‐indexed values.